TYPES OF ACTIVITIES INCLUDED IN THE CATEGORY OF HOUSEHOLD SERVICES PROVIDED TO THE POPULATION IN THE REPUBLIC OF UZBEKISTAN - Salahiddin Toshmatov Zayniddinovich; Asror Suyunov Bakhtiyorovich (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the socio-economic significance, content and essence of the development of the service sector, the structural changes implemented in the sector, the types and description of services according to the classification symbols, and the specific features and principles of the effective development of the service sector are researched.